A case of lead migration after sacral neuromodulation with erosion into the rectum - Bridget S. Kastelberg; Madeline C. Donnelly; George B. Smallfield, III; Stephen P. Sharp; Laura R. Carucci; Adam P. Klausner (Urology Case Reports)
We present a case of a 73-year-old female with medication refractory overactive bladder treated with the InterStim® sacral neuromodulation device. Five months post implantation she developed drainage over the lead site and rectal bleeding. Evaluation identified lead migration with rectal perforation requiring surgical removal of the battery and lead. Post removal, the patient returned to baseline urinary symptoms with the development of de novo fecal incontinence. This is the third reported case of sacral neuromodulation lead migration causing rectal perforation in the literature, and the only case managed with endoscopic closure of the rectal defect.